Covid Effects on the Returns to Schooling in Pennsylvania Industries - Chen, Yanan; Kelly, Kyle A.; Isgin, Ebru (Review of Economic Analysis, 2025)
This paper analyzes the effects of the COVID-19 recession on the rate of return to schooling for twenty industries in Pennsylvania. Using data from the American Community Survey 2011-2021, we find the rate of return to schooling declined by 0.3 percentage points during COVID years from its pre-COVID level, and COVID effects on the rate of return differed among industries in Pennsylvania. COVID increased the returns to schooling for three industries, decreased the returns to schooling for six industries, and had no effect on the returns to schooling for the remaining eleven industries. The changes in the rate of return to schooling reflect shifts in the wage premium between high- and low-wage workers.